DEVELOPING A TECHNO-FAMILY THROUGH VIRTUAL-REALITY BENTHIX GAME - Gamayanto, Indra; wibowo, Sasono (EDUTECH, 2020)
Â The development of information technology cannot separate from the family. It produces three classifications of the family: socio-family; media-family and techno-family. The problems that exist in techno-family: the pattern of parent education to the child, how parents oversee the use of social media owned by children, and how gaming can use as an educational pattern in improving family relationships. Furthermore, this journal uses the Johari window method, which is one method that can classify families into four family types. Thus, a formula for the techno-family is created: F = L.K2 and developed into seven stages and seven essential elements that can be applied to the family, to find out how mature the family is in educating especially in the field of technology information-social media-game, called the 7 stages of techno-family (the maturity level of family-technology). Knowing the weaknesses and strengths of a family is at the core of building and producing high-quality human resources that have the power of character that can provide positive benefits and contribution to the family life itself, society and the world. Techno-family is one of the solutions to change the culture and future inside the family.Â Perkembangan teknologi informasi tidak dapat dipisahkan dari keluarga. Ini menghasilkan tiga klasifikasi keluarga: sosio-keluarga; keluarga-media dan keluarga-tekno. Permasalahan yang ada dalam techno-family: pola pendidikan orang tua kepada anak, bagaimana orang tua mengawasi penggunaan media sosial yang dimiliki anak, dan bagaimana game dapat digunakan sebagai pola pendidikan dalam meningkatkan hubungan keluarga. Selanjutnya jurnal ini menggunakan metode Johari window yang merupakan salah satu metode yang dapat mengklasifikasikan keluarga ke dalam empat tipe keluarga. Maka dibuatlah formula techno-family: F = L.K2 dan dikembangkan menjadi tujuh tahapan dan tujuh unsur esensial yang dapat diterapkan pada keluarga, untuk mengetahui seberapa dewasa keluarga dalam mendidik khususnya dalam bidang teknologi. information-social media-game, yang disebut dengan 7 tahapan techno-family (tingkat kedewasaan keluarga-teknologi). Mengetahui kelemahan dan kekuatan sebuah keluarga merupakan inti dari membangun dan menghasilkan sumber daya manusia yang berkualitas yang memiliki kekuatan karakter yang dapat memberikan manfaat dan kontribusi positif bagi kehidupan keluarga itu sendiri, masyarakat dan dunia. Techno-family merupakan salah satu solusi untuk mengubah budaya dan masa depan dalam keluarga.